Penggunaan Media Flip Book dalam Meningkatkan Kemampuan Menulis Narasi Siswa pada Mata Pelajaran Bahasa Indonesia di Kelas IV SD Islam Al-Azhar 34 Makassar - Erniati Erniati; Sitti Nurjannah; Abu Bakar Tumpu; Herawati Arief S; Jumriati Jumriati (STKIP Andi Matappa Pangkep, 2020)
This research used Flip Book. Flip Book is a picture book with a media of the story is made interesting by using a nother paper for cover (flip) stories were included in the form of drawing or writing . in addition it is equipped with the creation of a wide variety of images in a sequence designed to facilitate students in describing the images and can be poured directly into written form. The stages in the use of media Flip Book is organized in working groups (batches formed heterogeneous), task planning group activities, implementing learning (collecting the results of the writing of the essay based on their creative ideas), prepare a final report (specify the message contained in the learning activities, evaluation of learning activities that have been implemented). From the research that has been carried out research , overall it can be seen that the application of media Flip Book greatly assist students in improving writing skills.